Bubble Formation Characteristic of Submerged Single-Hole Orifice in Aerosol Suspension - Sun, Qingyang; Gu, Haifeng; Yu, Xiang; Yin, Weikai (Frontiers in Energy Research, 2019)
Bubble columns are regarded as an effective containment filtration method. A large amount of radioactive aerosol will be retained in a liquid pool and generate decay heat. The surface tension, viscosity and other parameters of the liquid phase are affected by increasing temperature of the liquid pool and the presence of aerosol in the pool, which in turn affect the formation characteristics of bubbles. Another important factor affecting bubble generation characteristics is the proportion of steam in the gas phase, that is, the exchange of mass, and energy of gas phase. This paper will investigate the effects of liquid temperature, aerosol and gas phase composition on bubble formation characteristics by analyzing the variation of bubble detachment volume of the orifice in liquid pool.